Characterisation and disersal of bioaerosols emitted from composting facilities - Tamer Vestlund, Asli (Cranfield University, 2009)
The role of sustainable and natural waste management processes such as composting are increasingly becoming more important in tackling the current environmental challenge of the amount of waste that is being produced. However a potential risk of composting facilities is the release and dispersal of bioaerosols that might result in adverse health effects in sensitive receptors. Therefore, environmental regulators request regulatory risk assessments from composting facilities that are within 250m of sensitive receptors to assess the risk posed by bioaerosols. The prior art in compost related bioaerosol release and dispersal assessment is not extensive and gaps in the understanding of bioaerosols at source, on release from composting facilities and at receptor remain. Therefore, this research was undertaken to address some of these gaps in the current knowledge and to improve the understanding of the characterisation and dispersal of bioaerosols emitted from compost. Therefore firstly two studies were completed in regards to the characterisation of bioaerosols emitted from compost, in particular in improving the understanding of their aggregation and size distribution. In this context, a novel methodology (the compost tumbler) was developed to release and measure bioaerosols in experimental conditions. Data was generated using a combination of culturing and scanning electron microscopy methods to characterise the aggregation and size distribution of bioaerosols emitted from compost. Secondly, site work was conducted to validate the results of these controlled experiments and characterise the aggregation and size distribution of bioaerosols emitted from composting facilities. These controlled experiments and site work showed evidence of aggregation in bioaerosols released from compost. However, the majority of these bioaerosols were in single cell units hence they are more likely to be dispersed for longer distances. Following this, other studies were conducted in regards to the dispersal of bioaerosols emitted from compost, in particular in improving the understanding of bioaerosol concentration prediction by air dispersion modelling. Firstly preliminary air dispersion modelling was completed to assess the ability of a commercial air dispersion model,ADMS 3.3, to predict bioaerosol emissions from composting facilities compared to bioaerosol concentrations measured by on-site downwind bioaerosol sampling. Folowing this, the sensitivities of ADMS 3.3 were analysed and the effect of different modelling parameters on predicted bioaerosol concentrations were assessed. Finally, a final assessment of the potential of ADMS 3.3 to predict bioaerosol emissions from composting facilities was conducted. The overall results from the modelling studies indicated that ADMS 3.3 was not able to consistently predict absolute downwind bioaerosol concentrations at composting facilities. However it was also concluded that ADMS 3.3 can be a useful tool for the initial screening and assessing relative changes of bioaerosols at a compost facility, provided that the detailed assessment of absolute bioaerosol emissions are made in conjunction with measurement of downwind bioaerosol concentrations. The research presented in this thesis makes a significant contribution to knowledge in terms of improving the understanding of the characterisation and dispersal of bioaerosols emitted from composting facilities.